ANALYSIS OF SEVERAL DNA BARCODES FOR IDENTIFICATION OF Desmodium styracifolium - Bich Hong, Ha; The Huong, Nguyen; Van Viet, Nguyen (Journal of Forestry Science and Technology, 2021)
DNA barcoding is a short DNA fragment, is used to distinguish between species, especially morphologically similar species and processed specimens that are difficult to distinguish species. For plants, the regions of DNA used as barcodes in identification or taxonomy are usually sequences of the chloroplast genome and the nuclear genome, including the coding regions and the non-coding regions. In this study, three DNA barcode sequences, matK, rcbL, and ITS were used to evaluate the ability to distinguish Desmodium styracifolium species. The results of analysis and comparison of DNA barcode sequences in D. styracifolium with species of the same genus Desmodium showed that ITS had the highest similarity with Desmodium styracifolium species in Genbank (100%), followed by matK with 99.53%, and rbcL with 98.60%. The tree diagrams showing the phylogenetic relationship show that the studied samples are most similar to Desmodium styracifolium. Thereby, it shows that the use of DNA barcode sequences for species identification is very effective, in which the use of several DNA barcode sequences together will increase the reliability of the assessment results. The matK, rcbL, and ITS sequences were deposited in Genebank with accession numbers MW789613, MW789614, and MW315931, respectively, to contribute to the construction of the barcode DNA database for plant species.